Fibroblast Growth Factor 23 Is Associated With Carotid Plaque Presence and Area. Issue 9 (September 2015) - Shah, Nirav H.; Dong, Chuanhui; Elkind, Mitchell S.V.; Sacco, Ralph L.; Mendez, Armando J.; Hudson, Barry I.; Silverberg, Shonni; Wolf, Myles; Rundek, Tatjana; Wright, Clinton B.
<x xml:space="preserve">Abstract</x> Objective— Elevated fibroblast growth factor 23 (FGF23), a hormone that regulates phosphate homeostasis, has been associated with mortality, cardiovascular events, and stroke, and to arterial calcification in chronic kidney disease, but its role in atherosclerosis is unclear and population-based studies are lacking. We hypothesized that elevated FGF23 would associate with carotid plaque presence, area, and echogenicity in the race/ethnically diverse community-based Northern Manhattan Study (NOMAS) sample. Approach and Results— There were 1512 stroke-free NOMAS participants with FGF23 and 2-dimensional carotid ultrasound data (mean age, 68±9 years; 61% women; 62% Hispanic, 18% black, and 18% white). We used multivariable linear and logistic regression to evaluate FGF23, continuously and by quintiles, as a correlate of carotid plaque, plaque area (cubic root transformed), and echogenicity adjusting for sociodemographic and vascular risk factors. Participants with FGF23 levels in the top quintile were more likely to have carotid plaque (odds ratio, 1.49; 95% confidence interval, 1.02–2.19; P=0.04) and larger plaque area (β=0.32 mm2, 95% confidence interval, 0.10–0.53 mm2; P=0.004) than those in the lowest quintile, adjusting for estimated glomerular filtration rate, demographics, and vascular risk factors. Linear regression models also showed that log transformed FGF23 (LnFGF23) associated with greater odds of plaque presence (odds ratio, 1.26 per LnFGF23; 95% confidence interval, 1.01–1.58; P=0.04), and plaque area (β=0.19 mm2 per LnFGF23; 95% confidence interval, 0.07–0.31 mm2; P=0.002). Conclusions— Higher FGF23 associated with greater likelihood and burden of carotid atherosclerosis independent of CKD. Atherosclerosis may be a mechanism through which FGF23 increases cardiovascular events and stroke.